PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN (STUDI KASUS PADA PT. ULTRAJAYA MILK,Tbk) - Fina Diana (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to determine the effect of turnover on the level of profitability at PT Ultrajaya Milk Tbk. In this study, the turnover of capital is a free variable that is measured by how many times the turnover (times) and profitability are dependent variable that is measured by the percentage (%). The data used in this research is secondary data obtained from the Indonesia Stock Exchange in the form of Representatives Makassar balance sheet and income statement for the five years from 2009 to 2013 which is the latest data. Data collection was performed by the method of documentation. Data analysis was performed using ratio analysis, simple linear regression analysis, correlation analysis and t-test. The results of the regression equation obtained between the turnover of capital to the level of profitability, Y = 2,594 - 0,193X, which means that the constant value obtained for 2,594 is the amount of profitability that can be achieved regardless of the level of turnover. Furthermore, the value of the regression coefficient of -0.193 (X), which means that any capital turnover 1 times there will be a decline in the profitability of 0.193%. Results of correlation analysis was obtained r = 0.080, which means that the magnitude of the correlation between working capital turnover with very weak profitability. So there is a negative correlation between turnover and profitability, meaning that if the working capital turnover rate rises, the profitability declined. The calculations show that the effect of turnover on profitability is 6%, while the remaining 94% is determined by other factors not examined in this study.